2019
DOI: 10.1177/2165079919857447
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Impact of Work-Related Stress Among HIV/AIDS Health Care Providers in Guangxi, China: A Qualitative Research

Abstract: Work-related stress can negatively impact health care providers’ (HCPs) ability to provide care. We examined the sources of work-related stress experienced by HCPs who provided medical care for people living with HIV/AIDS and the impact of the stress on HCPs’ well-being and work performance. We conducted in-depth interviews with 46 HIV/AIDS HCPs in Guangxi, China. The interviews were audio-recorded, transcribed, and imported into NVivo V.11 for data management and data analysis using a thematic approach. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Our study indicates several adverse effects of work-related stress, including problems in emotion regulation, sleep, somatic health, work quality, and relationship with family members. This finding is consistent with previous studies that showed a substantial impact of work-related stress on health care providers working with HIV/AIDS or other diseases, affecting their emotional stability, 3 individual well-being (digestive disorders, cardiovascular disorders, sleep disorders, and poor immunity function), family and social life, 16 , 31 , 32 and quality of care. 16 The health status of health care workers has been found to have a moderate direct positive effect on the quality of health care.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study indicates several adverse effects of work-related stress, including problems in emotion regulation, sleep, somatic health, work quality, and relationship with family members. This finding is consistent with previous studies that showed a substantial impact of work-related stress on health care providers working with HIV/AIDS or other diseases, affecting their emotional stability, 3 individual well-being (digestive disorders, cardiovascular disorders, sleep disorders, and poor immunity function), family and social life, 16 , 31 , 32 and quality of care. 16 The health status of health care workers has been found to have a moderate direct positive effect on the quality of health care.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies that showed a substantial impact of work-related stress on health care providers working with HIV/AIDS or other diseases, affecting their emotional stability, 3 individual well-being (digestive disorders, cardiovascular disorders, sleep disorders, and poor immunity function), family and social life, 16 , 31 , 32 and quality of care. 16 The health status of health care workers has been found to have a moderate direct positive effect on the quality of health care. 33 Protection motivation theory (PMT) suggests that when health professionals are in good health, they usually provide better health care for patients, especially if they receive service health education and understand health-related behaviors.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations